2019
DOI: 10.1007/s40519-019-00771-z
|View full text |Cite
|
Sign up to set email alerts
|

Bulimic symptoms in a sample of college women: disentangling the roles of body size, body shame and negative urgency

Abstract: Purpose This study set out to disentangle the roles of body size, body shame and negative urgency on bulimic symptomatology in a sample of college women. We predicted that body shame would mediate the relationship between body size and bulimic symptomatology: with increasing body size, the greater would be the experience of body shame and, in turn, the greater the bulimic symptomatology. We also predicted that negative urgency would exacerbate this mediation pathway, and that the moderated mediation model woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…The scale has shown acceptable reliability in past studies [e.g. (Dalley et al, 2020); Cronbach's a 5 0.77]. In the current study, the scale demonstrated acceptable reliability (Cronbach's a 5 0.75).…”
Section: Methodssupporting
confidence: 50%
“…The scale has shown acceptable reliability in past studies [e.g. (Dalley et al, 2020); Cronbach's a 5 0.77]. In the current study, the scale demonstrated acceptable reliability (Cronbach's a 5 0.75).…”
Section: Methodssupporting
confidence: 50%
“…As we know that when an individual perceives that his or her body is unwelcome, which could cause a negative emotion ( Dalley et al, 2020 ). Based on the self-objectification theory, the internalization of feminine appearance ideals elicits body-related self-conscious emotions (i.e., body-related shame and body-related guilt, etc.…”
Section: Introductionmentioning
confidence: 99%